Structural behavior of FRP grid reinforced geopolymer concrete sandwich wall panels subjected to concentric axial loading. (15th August 2021) - Kumar, Sushil; Chen, Binqi; Xu, Yuye; Dai, Jian-Guo
Abstract: A new type of precast concrete sandwich wall panel, consisting of two basalt fiber reinforced polymer (FRP) reinforced geopolymer concrete wythes and an insulation layer, which are connected with hollow tubular glass FRP connectors, is studied in this paper. Ten sandwich wall panels were prefabricated and subjected to concentric axial loading. The primary test variables included slenderness ratio of the wall panel (i.e., the effective height to total sectional thickness ratio), longitudinal spacing of connectors, and the ratio of the wythe thickness to the insulation layer thickness of the wall panel. The load–deflection relationships, failure modes, and load–strain relationships were carefully investigated. All the wall panels failed by crushing of concrete. The connectors were subjected to axial force, transverse shear and bending in order to allow two wythes to deform together. The axial load capacity of the wall panel was reduced by 26% as the slenderness ratio varied from 8 to 17. The spacing of FRP connectors was found to have a marginal impact on the axial load capacity because of the existence of capping beams at the end of panels. An increase in the insulation thickness while keeping the wythe thickness constant resulted in a significant rise in the ultimate axial load in the case of panels having a higher slenderness ratio. A theoretical second-order analysis was performed to predict the ultimate axial load of equivalently assumed solid wall panels, and the predicted results were compared with the experimental ones.